Superstitions : a handbook of folklore, myths, and legends from around the world - McElroy, D. R. (Debra R.) (Wellfleet Press, 2020)
"Superstitions: A Handbook of Folklore, Myths, and Legends from around the World is your definitive reference to the history of superstitions, traditions, myths, and folklore from around the world"--